Does affirming children's autonomy and prosocial intentions help? A microtrial into intervention component effects to improve psychosocial behavior. (February 2022) - de Mooij, Brechtje; Fekkes, Minne; van den Akker, Alithe L.; Vliek, Lilian; Scholte, Ron H.J.; Overbeek, Geertjan
Abstract: Prior research has related children's prosocial behavior to overall well-being, and stimulating prosocial behavior is the aim of many social-emotional skills interventions. This study assessed if affirming children's autonomy stimulates their psychosocial behavior. We conducted a three-arm microtrial with four repeated measures to assess if a social-emotional skills intervention with an autonomy affirmation component had an additive effect on children's behavior as compared to a "regular" intervention focused exclusively on teaching social-emotional skills and a no-treatment control condition. Our sample consisted of 779 children in Grades 4–6 ( M age  = 10.61, SD  = 0.93). Findings from latent change modeling demonstrated that the social-emotional skills intervention with an autonomy affirmation component yielded superior effects as compared to the "regular" intervention and the no-treatment control condition on the improvement of internalizing and externalizing problem behavior in the three-month period after the intervention. The intervention with autonomy affirmation did not yield superior effects on prosociality and social skills, self-efficacy, and self-esteem or self-perceived competence. The absence of these effects may be attributed to the dosage of the interventions implemented—the affirmation of children's autonomy may require more than four sessions to sort observable effects. Overall, however, the findings of this study provide an initial suggestion that it may be beneficial to affirm children's autonomy and prosocial intentions when enhancing children's behavior.